Spasmophilia - S.K Hendarto; S. Lazuardi; B. Madyono; M. Affandi; Jos Utama (Paediatrica Indonesiana, 1978)
Sixty eight cases of spasmophilia were studied, consisting of 44 girls and 24 boys, the age ranging from 7 to 12 years. The most prominent symptom was cephalgia. Other symptoms included cramps, fainting attacks, abdominal pains, myalgia, breathing difficulties, palpitation, precordial pain, tremor and learning problems. Laboratory examination showed that most of them were hypocalcemic with prolonged Qo - Tc interval in electrocardiogram. BEG showed a certain pattern of increased thetha waves with irregular background activities and nonspecific changes. Treatment with calcium showed good clinical results. There seems to be no correlation between clinical improvement of symptoms and EMG findings.